Low-Molecular-Weight RNAs of Murine Sarcoma Virus: Comparative Studies of Free and 70S RNA-Associated Components - Emanoil-Ravicovitch, R. (1973)
Several low-molecular-weight RNAs were released from mouse leukemia sarcoma virus 70S RNA under conditions of thermal denaturation. One of them, the 70S-associated 8S RNA, exhibits a number of structural properties characteristic of a previously described free viral 8S RNA. This similarity was revealed by polyacrylamide gel electrophoresis and nucleotide composition.